2014
DOI: 10.1017/s0022381613001382
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian Assistance and the Duration of Peace after Civil War

Abstract: The principles of humanitarian assistance dictate that aid be distributed in accordance with need while remaining neutral with respect to the political stakes. However, these principles have unique implications in the postconflict context, where need is often correlated with opponents' performance in the previous contest. In these cases, humanitarian assistance is likely to be biased towards the conflict loser. Using a crisis-bargaining framework, this article describes a simple logic for how humanitarian aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Following previous work (Narang ), I estimate the amount of humanitarian aid disbursed in each conflict‐year using the OECD data on Official Development Assistance (ODA) . To be classified as humanitarian, aid must be designed to save lives and alleviate suffering during and in the aftermath of emergencies, while it must also be consistent with the humanitarian principles of humanity, impartiality, neutrality, and independence.…”
Section: Research Design and Datamentioning
confidence: 99%
“…Following previous work (Narang ), I estimate the amount of humanitarian aid disbursed in each conflict‐year using the OECD data on Official Development Assistance (ODA) . To be classified as humanitarian, aid must be designed to save lives and alleviate suffering during and in the aftermath of emergencies, while it must also be consistent with the humanitarian principles of humanity, impartiality, neutrality, and independence.…”
Section: Research Design and Datamentioning
confidence: 99%
“…My analysis suggests that the violence-inducing effect of aid can be explained by the capacity explanation, which states that aid may em-power rebels and fuel further violence (e.g. Narang, 2014). This finding also provides a refinement to the theory.…”
Section: E V E L O P M E N T a I Dmentioning
confidence: 66%
“…Its effectiveness, however, has been a subject of debate among scholars and policy makers alike. While some empirical studies have shown that aid is effective in deterring or ending violent conflicts (Bazzi and Blattman, 2014;Collier and Hoeffler, 2002a;de Ree and Nillesen, 2009;Savun and Tirone, 2012), some have found it ineffective or, in some cases, counterproductive (Crost, Felter, and Johnston, 2014;Dube and Naidu, 2015;Narang, 2014;Narang, 2015;Nunn and Qian, 2014;Sollenberg, 2012;Wood and Sullivan, 2015).…”
Section: E V E L O P M E N T a I Dmentioning
confidence: 99%
See 2 more Smart Citations